2017
DOI: 10.4103/ijccm.ijccm_304_16
|View full text |Cite
|
Sign up to set email alerts
|

Gender-based assessment of survival in trauma-hemorrhagic shock: A retrospective analysis of Indian population

Abstract: Introduction:Trauma-hemorrhagic shock (THS) is a leading cause of death. Female rats and women experience better outcomes in terms of survival after major trauma as compared to males. There are limited data in Indian population. Authors studied the gender-based outcome of patients with Class IV hemorrhagic shock due to blunt trauma and the distribution of factors among males and females which are known to affect outcome.Materials and Methods:It was a retrospective study with data of trauma victims between Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…This suggests that the female sex steroid hormones may have a protective effect in trauma [7, 25]. The apparent female advantage [26] and differences in survival with age [27] have led to the consideration of the role of the sex steroid precursor hormone DHEA, whose levels decline with age and differ between the sexes.…”
Section: Reviewmentioning
confidence: 99%
“…This suggests that the female sex steroid hormones may have a protective effect in trauma [7, 25]. The apparent female advantage [26] and differences in survival with age [27] have led to the consideration of the role of the sex steroid precursor hormone DHEA, whose levels decline with age and differ between the sexes.…”
Section: Reviewmentioning
confidence: 99%
“…It is a life-threatening condition and a leading cause of potentially preventable death among patients with trauma. 1 Early recognition of HS and appropriate intervention can save many lives and increase the survival rate of patients. Therefore, effective resuscitation strategies have become the key in the efforts to reduce mortality and to improve outcomes based on timely surgical hemostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with our results, this difference between females and males was no longer significant in multivariable regression analysis. 4 However, these results conflict with those of Desari and Verma et al 13,22 Focusing on sex-based differences in trauma outcomes in India and the USA, Desari et al demonstrated higher adjusted odds of mortality in males compared to females in both countries. 13 Verma et al specifically focused on Indian patients presenting with Class IV haemorrhagic shock and found an overall survival advantage in females on adjusted analysis.…”
Section: Discussionmentioning
confidence: 93%
“…19,20 This stratification was performed to assess whether years during which females are predicted to have higher oestrogen levels were associated with increased survival. In-hospital 30-day mortality was also compared using chi-squared analysis for males vs females stratified by the following ISS categories: mild injury (ISS <9), moderate injury (ISS 9-15), severe injury (ISS [16][17][18][19][20][21][22][23][24][25], and profound injury (ISS >25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation